Multi-dimensional influence of financial innovation on social and economic development - Huang, Juntao (Transactions on Economics, Business and Management Research, 2024)
As the core driving force of the development of modern financial system, financial innovation is profoundly changing the face of the financial industry by introducing new technologies, new services, new products and new models, and has a multi-dimensional and deep-seated impact on social and economic development. The purpose of this paper is to comprehensively explore the role of financial innovation in promoting economic growth, optimizing resource allocation, stimulating market vitality, improving financial service efficiency, promoting industrial upgrading, and facing challenges and coping strategies, with a view to providing theoretical reference and practical guidance for policy makers, financial institutions and all sectors of society.